Further Research in Food Processing Safety and Quality from Field to Fork (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
The global population is continuously growing, increasing the demand for food production. While agricultural innovations support this goal, food safety is often overlooked. Additionally, the nutritional value of food changes during storage, highlighting the need for efficient contaminant monitoring and sensitive detection techniques to track harmful substances. Advances in green extraction methods, pesticide residue analysis, and novel sensor technologies are essential for addressing contemporary food safety challenges. This Special Issue presents research on advanced methodologies for detecting and mitigating contaminants such as pesticides, mycotoxins, and heavy metals, while also examining the effects of pretreatment, processing, and storage on food quality and safety. Emphasis is placed on sustainable extraction techniques for agro-industrial byproducts and the development of innovative materials and sensors for real-time monitoring. Collectively, these contributions underscore the importance of integrating advanced technologies and interdisciplinary approaches to ensure safe, high-quality food from field to fork.